Analisis Du Pont System dalam Penilaian Kinerja Keuangan Perusahaan: Studi pada Perusahaan Sub Sektor Rokok yang Terdaftar di BEI Periode 2019-2023 - Delsa Eka Putri (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the financial performance of tobacco sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023 using the Du Pont System method. The approach used is quantitative descriptive with the population being all tobacco sub-sector companies on the IDX during that period. The sample was taken using purposive sampling, namely four companies with complete financial report data for five consecutive years. Data were collected through annual financial report documentation and analyzed using the five main ratios of the Du Pont System: Net Profit Margin (NPM), Total Asset Turnover (TATO), Return on Investment (ROI), Equity Multiplier (EM), and Return on Equity (ROE). The results of the study show fluctuations in financial performance, particularly in profitability, while asset efficiency and capital structure are relatively stable with indications of recovery in 2023. Medium-sized companies showed better adaptation and growth than large companies in facing market challenges. PT Hanjaya Mandala Sampoerna Tbk recorded superior performance based on Du Pont ROE, supported by high values for NPM, TATO, and ROI, although EM was relatively high. Overall, most tobacco sub-sector companies on the IDX showed good financial performance compared to industry standards, except for ITIC, which needed improvement. This study provides important insights for stakeholders in assessing the financial performance dynamics of the cigarette sub-sector in Indonesia.